Case Pedagogy in Initial Teacher Education: An Analysis of its Contribution to the Development of Professional Competences for Autonomy - Manuel Jiménez Raya; Borja Manzano Vázquez (Studies in Self-Access Learning Journal)
Case pedagogy is advocated in teacher education for autonomy as a teacher development strategy which can empower (student) teachers to understand and explore the implementation of pedagogy for autonomy. In an initial teacher education module implemented at the University of Granada (Spain), cases have become a crucial tool for promoting student teachers’ professional development towards teacher and learner autonomy. One of the strategies used in the module engages student teachers in exploring the implementation of pedagogy for autonomy during their internship and writing a case narrative on their pedagogical intervention. The present paper analyses six cases developed by student teachers during their internship to examine the dimensions of professional competence towards teacher and learner autonomy identified by Jiménez Raya et al. (2017) that they developed during case construction. These dimensions include 1) developing a critical view of (language) education, 2) centring teaching on learning, 3) managing local constraints to open up spaces for manoeuvre, and 4) interacting with others in the professional community.